The Benefit non-take-up in the Context of Cash Social Assistance Reform in Lithuania - Gabnytė, Vitalija; Vencius, Tautvydas; Navickė, Jekaterina (Socialinė teorija, empirija, politika ir praktika, 2020)
The purpose of this article is to present the results of cash social assistance (CSA) benefit non-take-up in the context of the CSA system reform in Lithuania. The right to adequate minimum income benefits is one of the 20 key principles under the European Pillar of Social Rights (EPSR). Using the tax-benefit microsimulation model EUROMOD we seek to identify all those eligible to CSA benefit and to analyse its non-take-up rates in Lithuania. The analysis for 2016 showed that CSA benefit non-take-up in Lithuania was around 22%. This means that around one fifth of those who are entitled to this benefit do not get it for various reasons. The results show that there are two types of households, with a non-take-up rate exceeding 30%: single person and lone parent households. The dynamics of CSA benefit non-take-up between 2007-2016 were strongly negatively correlated to the annual average number of recipients of the CSA benefit. This makes for a counter-cyclical dynamic of the CSA non-take-up relative to the economic growth cycle. We find some evidence of an increase in the CSA non-take-up rate following the recent CSA reform in Lithuania. Further analysis is needed to distinguish between the effects of the economic cycle and the CSA reform.